Mobilizing satisfied users for promoting family planning final report on a pilot study in the eastern Visayas region of the Philippines - Soledad, Daisy R.; Barloso, Wilfred G.; Mateo, Domingo A.; Abilar, Antonio A.; Mondragon, Dominador B. (1997)
The project described here attempted to increase prevalence of use of more effective family planning methods (MEM) and of contraceptive practice in general in large, geographically dispersed barangay supply point (BSP) areas in Region 8 of the Philippines. Sixty volunteer motivators were selected and trained, using a modified version of the BSP officers' training curriculum with emphasis on motivational aspects. An experimental design with two experimental groups and a control group (randomly allocated) was employed.